Analisis Penerapan Akuntansi Pertanggungjawaban dalam Pengelolaan Dana Hibah di Lembaga Kesejahteraan Sosial Ummu Syahidah Gorontalo - Abdullah, Yulianti; Nilawaty Yusuf; Ronald S. Badu (Institute Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2023)
This study aimed to assess the extent to which accountability accounting is applied in the management of grant funds at the Ummu Syahidah Social Welfare Institution. The research method employed was descriptive qualitative. Data collection was carried out using observation, interviews, and documentation studies techniques. The Result of the study revealed that the implementation of responsibility accounting in the management of grant funds at the Ummu Syahidah Social Welfare Institution adhered to the requirements for responbility accounting and the interpretation of Financial Accounting Standars (ISAK 35), particularly in terms of organizational structure, planning/budgeting,implementation/control which were found to be properly implemented. However, the institution has yet to carry out cost classification/acoount code preparation and presentation of financial reports. Therefore, it is recommended that the institutions optimize the fulfilment of grant management requirements to establish trust among all paties